Kendala Implementasi Kurikulum Merdeka Pada Guru Otomotif SMK Kristen 5 Klaten: Inggris, Indonesia - Ari Setiawan; Joko Sriyanto (Journal of Automotive Technology and Education, 2025)
Abstract This study aims to identify and analyze the challenges faced by automotive teachers in implementing the Merdeka Curriculum at SMK Kristen 5 Klaten. The research employed a qualitative descriptive method, with data collected through in-depth interviews and documentation. The respondents consisted of 10 automotive teachers from the TKRO, TBSM, and TBO programs. The findings reveal several main issues faced by the teachers: 1) lack of understanding of the essence and concept of the Merdeka Curriculum; 2) difficulties in designing, implementing, and evaluating differentiated learning; 3) low discipline among students and teachers during learning activities, as well as limited teacher ability to analyze the condition of school equipment; and 4) limited support for training and technical assistance.   Abstrak Penelitian ini bertujuan mengidentifikasi dan menganalisis kendala yang dihadapi guru otomotif dalam implementasi Kurikulum Merdeka di SMK Kristen 5 Klaten. Metode yang digunakan adalah deskriptif kualitatif dengan teknik pengumpulan data melalui wawancara mendalam dan dokumentasi. Responden berjumlah 10 guru otomotif dari program TKRO, TBSM, dan TBO. Hasil penelitian menunjukkan bahwa guru menghadapi beberapa permasalahan utama, yaitu: 1) kurangnya pemahaman guru terhadap esensi dan konsep Kurikulum Merdeka; 2) kendala dalam merancang, melaksanakan, serta mengevaluasi pembelajaran berdiferensiasi; 3) rendahnya kedisiplinan siswa dan guru dalam pelaksanaan pembelajaran serta keterbatasan kemampuan guru dalam menganalisis kondisi peralatan sekolah; dan 4) keterbatasan dukungan pelatihan dan pendampingan teknis.